In-vitro Antibacterial Activity of Sri Lankan Traditional Rice (Oryza sativa L.) Extracts against Bacteria Causing Skin and Soft Tissue Infections - Godakumbura, P.I.; Kariyawasam, T.I.; Arachchi, P.M.; Fernando, N.; Premakumara, S. (Journal of Pharmacy Research, 2016)
Attached

The aim of this study was to evaluate the potential antibacterial activity o f the extracts o f selected parboiled and un-parboiled Sri Lankan traditional rice against bacteria causing skin and soft tissue infections. Methanolic extracts o f five Sri Lankan traditional rice including Kalu Heenati, Pokkali, Rathdal, Kahawanu and Sudu Murunga were used for in vitro antibacterial analysis. Antibacterial activity was evaluated in both the parboiled and un-parboiled rice samples. Concentrations o f rice extracts used for the assays were 1000 pg/mL and 2000 pg/mL from the each extract. The antibacterial activity was evaluated against common bacteria causing skin and soft tissue infections (Staphylococcus aureus (ATCC 25923), Pseudomonas aeroginosa (ATCC 27853), Escherichia coli (ATCC 25922) and three clinical isolates o f Methicillin resistant staphylococcus aureus (MRSA)) by well diffusion method and viable colony count technique. According to the results, methanolic extracts o f all the selected Sri Lankan traditional rice varieties exhibited a potent antibacterial activity against Staphylococcus aureus with minimum bactericidal concentrations (MBC) o f200 pg/mL (minimum incubation time (MIT); 30 min) for Rathdal, 200 pg/mL(MIT; 60 min) for Kalu Heenati, Pokkali and Kahawanu, and 2000 pg/mL(MIT; 60 min) forSudu Murunga. The largest inhibition zones were observed in the extracts o f Kalu Heenati and Rathdal. Kalu Heenati, Pokkali and Rathdal showed an efficacious inhibitory effect against MRSA (MBC; 200 pg/mL, MIT; 60 min), whereas the highest inhibitory activity was observed for Rathdal. Only the extract of Kalu Heenati was slightly active against Pseudomonas aeroginosa. None o f the rice extracts studied showed an antibacterial activity against Escherichia coli.Reduction and loss o f antibacterial activity was detected in rice after subjected to parboiling. In conclusion, Sri Lankan traditional rice varieties with red pericarp are good sources o f antibacterial compounds m ainly against Gram positive bacteria. M ethanolic extract o f Rathdal and Kalu Heenati showed a high efficacious inhibitory effect against skin and wound pathogens o f Staphylococcus aureus and MRSA.
Keywords: Traditional rice; Parboiled; Antibacterial activity; Skin and soft tissue infections